An apparatus and methodology for high-power SQUID-detected ferromagnetic resonance measurements - Stamenov, Plamen; O'Reilly, James M. (My University, 2019)
Historically, ferromagnetic resonance has been dominated by inductive techniques, for the best part of the last 80 years. It has been only in the last 20 years that non-inductive techniques, such as Ferromagnetic Resonance Force Microscopy (FMRFM) and Magneto-optical Kerr Effect (MOKE), have been used to study, for example, the spatial distribution of resonance modes. Neither of these techniques is absolute - i.e. provides information on the amplitude of excitation as a function of absorbed microwave power. Here we extend on the recent demonstration of SQUID-detected FMR [J. M. O’Reilly and P. Stamenov, Rev. Sci. Instrum. 89, 044701 (2018)], of absolute scalar resonance measurements in single-crystalline and poly-crystalline YIG, at various fields and temperatures, by introducing a new set-up, where the microwave power, instead of being sunk in a matched load at the cryogenic end of the measurement probe is brought back to the ambient environment and is both metered and sunk in high dissipation power (>50 W @ 50 Ω) matching load. The here suggested methodology allows for the absolute excitation amplitude of modes excited during high-power operation of critical microwave devices, such as filters and Y-junction stripline circulators, to be predicted based on direct measurements of the same material in a known geometry.
Keywords: Ferromagnetic resonance; Magnetism; Squid susceptometer; Spectrum analyzers; Telecommunications engineering; Non linear dynamics; Microwave devices; ferromagnetic resonance